Prediction of the attenuation of a filtered custom earplug - Voix, Jérémie; Laville, Frédéric (Applied acoustics, 2009)
A method has been developed to predict the attenuation of an earplug when filtered by passive resistive elements (dampers). The method is based on the assumption that sound transmission paths traveling through the damper element and through the earplug are independent, hence their respective sound energies simply add to each other. This hypothesis was validated with measurements on both an acoustical test fixture and on human subjects, using a commercially available expandable custom earplug. This earplug features a sound-bore that can either be used for an F-MIRE (Field microphone-in-real-ear) attenuation measurement or be fitted with a damper in order to adapt the amount of attenuation to the wearer’s needs. The uncertainty associated with the proposed prediction method was formulated and quantified using REAT and F-MIRE attenuation measurements on human subjects. An initial experimental verification of the prediction method, on a limited number of subjects, has been successfully completed.